Analysis of nucleotide variants in the promoter region of the uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) gene among neonatal jaundice Malay infants without variations in the exonic regions - Ismail, Rosliza (2015)
Overproduction of bilirubin is one of the major factor which contributes to neonatal hyperbilirubinemia that is catalyzed by an enzyme Uridine glucuronyl transferase encoded by the UGT1A1 gene. This is a normal physiological occurance after birth. The objectives of this study were to i) determine the presence of variants or polymorphisms in the promoter region of the UGT1A1 gene amongst Malay infants with and without jaundice using high resolution melting (HRM) analysis and to assess the correlation between identified variants or polymorphisms using linkage disequilibrium analysis. All samples that were free from variant in the exonic regions were recruited from another study by Hasnah Ma’amor in year 2011. High resolution melting analysis was performed to screen for the promoter region in the UGT1A1 gene and for subjects who were identified to have different pattern of HRM analysis, sequencing was performed to confirm the presence of variant. SPSS was used for data analysis. Two hundred and fifty (250) infants who were undergone phototherapy and 260 infants who were not undergoing phototherapy were included in the jaundiced and non-jaundice groups. Six variants were investigated but two were not detected in this study. The most common variant was c.-3279T>G which is common in other Asian populations as well. All the variants detected in this study have been reported as SNPs in Indian, Caucasion and Japanese populations. The c.-3279T>G variant had been identified as the most common variant in 163 jaundice Malay patientsin the promoter region of the UGT1A1 gene with the p-value 0.001 and is a risk factor for Malay neonatal hyperbilirubinemia.